Development of microwave sensing system to measure the sweetness and ripeness of pineapple - Abdullah, Suhail Najm (2015)
Sensors are the most effective tools used to integrate the industrial infrastructure that will lead in increasing the quality of the products. For industrial food companies sensors are playing a vital rule in producing healthy and natural food. This thesis represent a technique of microwave sensors. a microwave sensor to predict the moisture content of the pineapple fruit is developed. Then, the ripeness and sweetness of pineapple are estimated using conductivity and PH measurements respectively. Hence these can increase the quality of the fruit product if the system is used as a tool in the industrial fruit products. It will also extend the expiry date.